Factors associated with regular counselling attendance of HIV outpatients of a national referral hospital in Jakarta, Indonesia: a cross sectional study - M. Pane; E. I. Sianturi; Yin Mei Fiona Kong; Philip Bautista; Herlina; K. Taxis (BMC, 2018)
Abstract Background Counselling has been shown to improve adherence to medication in people living with HIV (PLHIV). The aim of this study was to investigate factors associated with regular counselling attendance of patients taking antiretroviral therapy (ART). Methods We conducted a cross-sectional, paper-based survey among 880 PLHIV patients on ART attending outpatient clinics of a referral hospital in Jakarta. Patients on ART, above 18 years old, providing written consent were included. The primary outcome was regular counselling attendance (i.e., having attended at least 3 sessions in the previous 3 months) using records from counsellors. Factors associated with regular counselling attendance were assessed using logistic regression analysis. Results The majority of patients were male (71.1%) and had regular counselling (78.4%). Being 31 to 40 years old (odds ratio (OR) = 0.55, 95% confidence interval (CI) = 0.32-0.93, > 40 years (OR = 0.30, 95% CI = 0.16-0.55) vs < 30 years, hepatitis B/C co-infection (OR = 0.42, 95% CI = 0.24-0.75), living > 20 km from the hospital (OR = 0.55, 95% CI = 0.33-0.93), transmission male-to-male (OR = 0.13, 95% CI = 0.04-0.44), unemployment (OR = 1.88, 95% CI = 1.02-3.44), part-time employment (OR = 10.71, 95% CI = 4.09-28.02), household member with HIV (OR = 3.31, 95% CI = 1.70-6.44), and Christianity (OR = 1.82, 95% CI = 1.12-2.94) were associated with regular counselling attendance. Conclusion This study suggests that counselling services should be reviewed to ensure that they are near home and fit the needs of older patients or patients with co-morbidities and minorities. Tailoring counselling may improve attendance.